Peran Yayasan dalam Pengembangan Pendidikan Madrasah Aliyah Darud Da’wah Wal’Irsyad Attaufiq Padaelo Barru - Hairati Anas; Hasibuddin; Syahid, Akhmad (Journal of Gurutta Education, 2023)
This study aims to determine the role of the foundation's organ, namely the chairman of the foundation's management, in the educational environment in the madrasa in the effort to develop education in the madrasah. This research was carried out at the Attaufiq Foundation and at the Madrasah Aliyah Darud da'wah Wal Irsyad Attaufiq Padaelo using descriptive and qualitative methods. The data collection techniques in this study used interviews, observation, and documentation techniques. The results of the study indicate that the foundation has a role as a policy maker, supervisor, supervisor and coach in the implementation of education development in madrasas. This can be seen from the direct role played by the foundation's organs for madrasas, such as being selective in accepting educators and education staff and strongly supporting all activities carried out by the madrasa head for the achievement of madrasa education development. The development of education in madrasas cannot be separated from adequate national education standards, which greatly guarantee the development of education in madrasas. Of course, there must be good cooperation and synergy between the head of the madrasa and the organs of the foundation in the development of the madrasa. It can be concluded that the role of the foundation in the development of Madrasah education at Madrasah Aliyah Darud'da'wah wal'Irsyad is quite good and effective. This shows that the foundation plays an important role in the development of madrasa education